PERSEPSI PASIEN HIPERTENSI TERHADAP KEAMANAN DAN EFEKTIFITAS OBAT TRADISIONAL UNTUK HIPERTENSI DI KABUPATEN BANYUMAS - Aulia Rahman; Dyah Aryani Perwitasari; Kintoko Kintoko; Suwijiyo Pramono (Fakultas Sains, Teknologi, dan Analsisi Institut ilmu Kesehatan Bhakti Wiyata, 2020)
Hypertension is the biggest risk factor for cardiovascular disease which is the first caused of death in the world. Besides lifestyle modification and pharmacological therapy, hypertension can also be treated using traditional medicine. The use of traditional medicine can be influenced by characteristics and perceptions. The purpose of this study was to determine the patient's perception of traditional medicine for hypertension in Banyumas Regency. The research was conducted in April 2019, the subjects were hypertensive patients who become member of PROLANIS in Banyumas Regency. The research design used a cross-sectional study with a purposive random sampling. Perception was measured using a questionnaire with a Likert scale from strongly disagree to strongly agree (scale 1-5) then converted into a percent index score. There were 340 respondents who participated in this study. The majority of respondents were women (56.8%) aged 45-60 years old (52.4%), with secondary education (55.3%), working (85%) and having moderate income (52.6%) . Respondents have a good perception of the safety and effectiveness of traditional medicines for hypertension with an average percent index score of 68.53% for safety and an 67.38% for effectiveness